Effects of immune checkpoint inhibitor associated endocrinopathies on cancer survival - Yang, Lisa; Murthy, Sruthi; Cortellini, Alessio; Lim, Emma A.; Gonzalez, Michael; Pinato, David J.; Abdel-Malek, Mariana; Mahmoud, Sarah; Martin, Niamh M. (Frontiers in Endocrinology, 2024)
Objectives: Immune checkpoint inhibitors (ICIs) are associated with immune-related adverse events (irAEs), of which endocrinopathies are common. We characterised endocrine and non-endocrine irAEs in cancer patients receiving ICIs, identified risk factors for their development and established whether endocrine and non-endocrine irAEs were differentially associated with improved cancer prognosis.Design and Methods: Single-centre, retrospective cohort study of patients with advanced or metastatic solid tumours receiving at least one ICI treatment cycle (242 men, 151 women, median age 65 years). Main outcome measures were incidence of any irAE during the study period, overall survival and time to treatment failure.Results: Non-endocrine irAEs occurred in 32% and endocrine irAEs in 12% of patients. Primary thyroid dysfunction was the most common endocrine irAE (9.5%) and the majority of endocrinopathies required permanent hormone replacement.Women had an increased risk of developing endocrine irAEs (p = 0.017).The biggest survival advantage occurred in patients who developed both endocrine and non-endocrine irAEs (overall survival: HR 0.16, CI 0.09-0.28). Time to treatment failure was also significantly improved in patients who developed endocrine irAEs (HR 0.49, CI 0.34 -0.71) or both (HR 0.41, CI 0.25 -0.64) but not in those who only developed non-endocrine irAEs.Conclusions: Women may have increased risk of endocrine irAEs secondary to ICI treatment. This is the first study to compare the effects of endocrine irAEs with nonendocrine irAEs on survival. Development of endocrine irAEs may confer survival benefit in ICI treatment and future, prospective studies are needed to elucidate this.